WAWASAN AL-QUR’AN TENTANG BUDAK (Upaya-Upaya Pembebasan Budak Dalam Islam) - Alimuddin Hassan Palawa (AL-FIKRA, 2008)
The Perspective of al-Qur’an on Slavery: Some Efforts to Combat Slavery in Islam: Men are basically created as the greatest creation in a free and independent condition. It is wrong if men restrict and restrain themselves towards others; moreover, if they worship the creation of God. Therefore, to avoid self-slavery towards human beings or towards disire, things, jobs, women and others, Alqur’an has taught people to worship the only God, the Creator. This is not to say that one has restrained himself towards self-slavery when God is the only One he worships. Indeed, it is by worshiping God that men even free and distance themselves from any forms of slavery.